Modeling blockchain technology in assessment management: the initial readiness investigation - Shuhaimi, Joharri; Awang, Hapini; Al-Mashhadani, Abdulrazak F. Shahatha; Jafar, Mohd Fairuz; Mansor, Nur Suhaili (International Journal of Evaluation and Research in Education (IJERE), 2025)
The implementation of the school-based assessment (SBA) came with a system as part of the effort to reduce the workload of teachers in managing the SBA. However, a traditional system is costly and heavily centralized, frequently leading to impediments, delays, irregularities and may even create opportunities for dishonest activities. To enhance the existing traditional system, integrating emerging blockchain technology (BC) is proposed. Given the challenges, complaints, and rejection faced by traditional assessment management systems, this paper presents a conceptual framework based on the technology acceptance model (TAM) and diffusion of innovation (DOI) to examine pre-university teachers’ perception of implementation and readiness to adopt BC-based project paper management (BPPM) which is subsequently verified through a qualitative study. This study employs a process that consists of three main steps: a thorough review of existing literature, thematic analysis, and the process of gathering and determining readiness factors. Teachers’ perspectives were successfully gathered from 59 pre-university teachers by posting semi-structured questions in a Telegram group of Malaysian pre-university teachers. The study found that most pre-university teachers support the BPPM implementation with the condition that the system can address two primary concerns: server scalability and confidentiality issues. The effectiveness of BPPM implementation depends on its capacity to meet user needs and expectations while delivering clear benefits, along with superiority compared with existing systems.